1983
DOI: 10.1212/wnl.33.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Phonological agraphia

Abstract: Two writing routes (phonological and lexical) have been postulated. We studied four patients who had disruption of the phonological route (ie, inability to write pronounceable nonwords) but with a preserved lexical route. Results showed that the phonological route has two components: segmentation and phoneme-grapheme conversion. Disruption of either function may induce phonological agraphia. The preserved lexical route uses a whole-word mechanism and is strongly affected by semantic factors, such as imageabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(62 citation statements)
references
References 0 publications
3
57
0
2
Order By: Relevance
“…Detailed psycholinguistic analysis based on the symptoms and lesion sites suggest that kanji-selective agraphia arises from an impaired access to visual graphic kanji images stored in long-term memory. This writing disorder is thought to be analogous to the lexical agraphia seen in Western languages (Roeltgen et al, 1983;Roeltgen and Heilman, 1984). Our findings complement the conventional view from lesion and fMRI studies that this area participates in the processing of kanji writing through orthographic retrieval, even with no accompanying overt motor execution (Soma et al, 1989;Nakamura et al, 2000).…”
Section: Functional Role Of the Left Pitc In Kanji Writingsupporting
confidence: 80%
See 1 more Smart Citation
“…Detailed psycholinguistic analysis based on the symptoms and lesion sites suggest that kanji-selective agraphia arises from an impaired access to visual graphic kanji images stored in long-term memory. This writing disorder is thought to be analogous to the lexical agraphia seen in Western languages (Roeltgen et al, 1983;Roeltgen and Heilman, 1984). Our findings complement the conventional view from lesion and fMRI studies that this area participates in the processing of kanji writing through orthographic retrieval, even with no accompanying overt motor execution (Soma et al, 1989;Nakamura et al, 2000).…”
Section: Functional Role Of the Left Pitc In Kanji Writingsupporting
confidence: 80%
“…Later, another type of agraphia was described: damage to the junction of the left angular gyrus and the parieto-occipital lobule produces lexical agraphia. This damage is attributable to a disruption in the whole-word retrieval system necessary to read orthographically irregular words (Roeltgen et al, 1983;Roeltgen and Heilman, 1984;Roeltgen, 1993). The study of functional differences in left hemisphere writing systems has thus, as yet, been based solely on studies of Western languages.…”
Section: Introductionmentioning
confidence: 99%
“…Phonological dyslexia and dysgraphia are written language disorders characterized by a disproportionate difficulty in processing non-words compared to real words, giving rise to an exaggerated lexicality effect in reading and spelling Dérouesné and Beauvois, 1979;Coltheart, 1996;Shallice, 1981;Roeltgen et al, 1983;Henry et al, 2007). Within the framework of dual-route models (Ellis, 1982;Patterson and Shewell, 1987;Ellis and Young, 1988;Shallice, 1988;Coltheart et al, 2001), these syndromes have been interpreted to reflect the selective breakdown of sublexical phoneme-grapheme conversion mechanisms with relative preservation of lexical-semantic procedures for reading and spelling.…”
Section: Introductionmentioning
confidence: 99%
“…Although there appears to be an association between phonological dyslexia/dysgraphia and damage to perisylvian cortical regions implicated in phonological processing, attempts to determine the critical lesion site have produced inconsistent and contradictory results. For instance, it has been suggested that posterior perisylvian lesions centering on the supramarginal gyrus may be the critical neural substrate of phonological dysgraphia (Roeltgen et al, 1983;Roeltgen and Heilman, 1984). However, this syndrome has also been described in patients with damage limited to anterior perisylvian cortical regions, including the frontal operculum/ precentral gyrus and insula (Marien et al, 2001;Rapcsak and Beeson, 2002;Henry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, semantic processing is thought to engage anterior and inferolateral temporal regions (BA 38,20,21) as well as inferior prefrontal cortex (BA 47), and the angular gyrus (BA 39;Binder & Price, 2001;Mummery et al, 2000;Vandenberghe et al, 1996). The phonological codes involved in spelling rely on a network of perisylvian cortical regions, including Broca's area, Wernicke's area, the supramarginal gyrus, and insula (Alexander et al, 1992;Fiez, 1997;Omura et al, 2004;Roeltgen et al, 1983). Orthographic knowledge of lexical representations for reading and spelling is thought to engage a critical region within temporo-occipital cortex (BA 37), sometimes referred to as the visual word form area (Beeson et al, 2003b;Cohen & Dehaene, 2004;Nakamura et al, 2002;Rapcsak & Beeson, 2004).…”
Section: Introductionmentioning
confidence: 99%